Mapping Approaches to Decolonizing and Indigenizing the Curriculum at Canadian Universities: Critical Reflections on Current Practices, Challenges, and Possibilities - Brunette Debassige, Candace; Wakeham, Pauline; Smithers-Graeme, Cindy; Haque, Aisha; Chitty, Sara Mai (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
This article identifies five predominant approaches to Indigenizing the curriculum occurring within Canadian universities today. Examining these approaches in relation to theories of change articulated by Gaudry and Lorenz (2018) and Stein (2020), the article considers the possibilities and limits of each approach as well as the degree to which they challenge the colonial and Eurocentric edifices of Canadian universities. While many of the current approaches to curricular change involve minor reforms that focus on individual transformation rather than substantive structural shifts, the authors also identify promising initiatives that push toward greater Indigenous intellectual sovereignty and institutional autonomy. The article concludes by calling on academic institutions to better center Indigenous Peoples, lands and knowledges in curricular change, and more specifically, to embrace structural revision that ensures Indigenous leadership and autonomy.